Dragørmålets lire ‘brudesvend’/‘brudepige’: Et hapax legomenon? - Krogh, Steffen; Robbe, Joost (Danske Studier, 2024)
This article investigates the etymology of the noun lire in the Dragør dialect of around 1840, which was spoken on the Danish island of Amager. The word lire designated ushers and bridesmaids at a wedding. The article clarifies the inflection of the word and discusses different pathways to explain its etymology. After having explored possible connections of lire to Norwegian lire and Dutch lier, the article argues that lire is connected to the Danish noun leder, which equally designated ushers and bridesmaids at a wedding in the dialects of Amager.